Evaluation of Extracranial Carotid Arteries by Duplex Ultrasound in Computed Tomography confirmed Ischemic Stroke and its correlation with brain parenchymal involvement - P, Sidharth; V, Binod Varghese; Joseph, Rani Ann; Harisuthan, (Nepal Journal of Neuroscience, 2025)
This study aimed to evaluate the relationship between carotid artery disease, infarct characteristics, and associated risk factors in patients with CT-confirmed ischemic stroke. The study included 50 participants, primarily aged 61-70 years (42%) with a mean age of 60.7 years, and a male predominance (78%). Hypertension, diabetes mellitus, and dyslipidemia were each prevalent in 68% of the sample. Most infarcts were located in the middle cerebral artery (MCA) territory (86%), with the combined cortical and sub-cortical regions being the most frequently affected (58%). A significant association was found between the severity of carotid stenosis and infarct size, with larger infarcts (>2 cm) predominantly occurring in patients with stenosis ≥70% (p = 0.001). The analysis of stenosis by age revealed that the 61-80 age group had the highest frequency of stenosis, primarily in the 1) and the presence of plaques were significantly associated with infarcts in the MCA territory and sub-cortical areas. Calcified plaques were particularly prevalent in these regions. Strong associations were also found between carotid lesions and risk factors such as hypertension, diabetes, dyslipidemia, smoking, coronary artery disease, and history of stroke. The